Did you mean: "find the roots of f(x) = x^2 - 12x + 44?"
If so, notice that a=1, b= -12 and c=44.
According to the quadratic formula,
-b plus or minus sqrt(b^2 - 4ac)
x = ----------------------------------------------
2a
Here, with a=1, b= -12 and c=44,
12 plus or minus sqrt([-12]^2 - 4[1][44])
x = -------------------------------------------------------
2[1]
This simplifies to
12 plus or minus sqrt(144-176)
x = -------------------------------------------
2
12 plus or minus sqrt( -32)
= ---------------------------------------
2
= 6 plus or minus 2i*sqrt(2)